Highly Efficient and Ultra‐Broadband Yellow Emission of Lead‐Free Antimony Halide toward White Light‐Emitting Diodes and Visible Light Communication. Issue 10 (3rd July 2022) - Mo, Qionghua; Yu, Jiabing; Chen, Chen; Cai, Wensi; Zhao, Shuangyi; Li, HaiYun; Zang, Zhigang
Abstract: Due to the broadband emission induced by self‐trapped excitons (STEs), low‐dimensional hybrid lead halides are regarded as an emerging class of highly efficient light emitters. However, the toxic lead element impedes their commercial application. Here, a new air‐stable hybrid lead‐free metal halide [Na(DMSO)2 ]3 SbBr6 with a 0D structure constituted by [SbBr6 ] octahedral and [Na(DMSO)2 ]3 units is synthesized at room temperature, which exhibits a high photoluminescence quantum yield of 60% and an ultra‐broadband yellow emission centered at 608 nm, with a full width at half‐maximum of 160 nm. First‐principles calculations and experimental studies unveil that the formation of STEs in this 0D structure contributes the broad emission. Then, warm white light‐emitting diodes (WLEDs) are proposed by combining blue LED chips with yellow [Na(DMSO)2 ]3 SbBr6, showing a color rendering index of 85, a correlated color temperature of 3603 K. Finally, the prepared WLEDs are utilized in visible light communication (VLC) with an achieved −3 dB bandwidth of 7.2 MHz and a high transmitted data rate of 81.6 Mbps by applying orthogonal frequency division multiplexing modulation with adaptive bit loading. This research not only enriches the family of perovskite related materials, but also inspires the potential of low‐dimensional metal halide in VLC. Abstract : A new air‐stable hybrid lead‐free metal halide [Na(DMSO)2 ]3 SbBr6 with ultra‐broadband yellow light emission and high photoluminescence quantum efficiency is fabricated. The excellent optical performance facilitates the applications of white light‐emitting diodes and visible light communication.